Rediseño de espacios interiores y su influencia en los procesos de aprendizaje del Centro Educativo “Numa Pompilio Llona” en la ciudad de Latacunga - Lema Panchi, Brenda Jazmin (2023)
The purpose of this research project is to study the spaces interiors of the Educational Center "Numa Pompilio Llona" located in Latacunga, the objective of this analysis is to improve the conditions of each space by identifying the problem, so that in this way the space where the student learns is optimal, for this it was necessary to carry out an investigation of the educational environments that are adequate, comfortable, that consider the population for which it is going to be designed and taking into account their way of learning The research takes into account interviews with teachers, professionals in design, psychologists, this has served as a contribution in the investigation and the elaboration of the proposal, in addition, observation sheets are made in order to have a point of view different from that of children and teachers. In the same way, measurements are made of each space educational, photographs, observations that show unfavorable conditions where the classrooms of the institution are located, so this creates problems in the student learning. Therefore, a proposal for intervention in the interior and exterior areas and furniture, creating environments that encourage learning.